Conjunctival Malignant Melanoma: Report of a Rare Case - Sathawane, Prajakta Ramhari; Poflee, Sandhya Vivek; Raut, Waman Krishnaji (Annals of Pathology and Laboratory Medicine, 2018)
ABSTRACT Ocular melanomas comprise 3.7 percent of all melanomas. Amongst ocular structures, melanoma of conjunctiva is an uncommon tumor and comprise around 5 percent of the melanomas in the ocular region. Non-bulbar conjunctival malignant melanomas (CMM) are rare and are associated with substantial morbidity and mortality. As the presentation varies, clinical diagnosis is missed in the early stages. When CMM are amelanotic, differentiating them from other epithelial lesions on the basis of morphological features becomes even more difficult. High index of suspicion on the part of histopathologist can achieve early diagnosis of CMM on the basis of characteristic biopsy findings. Confirmed diagnosis on the basis of histopathological examination (HPE) and immunohistochemistry (IHC) studies can lead to appropriate timely management in these cases.